Effects of Gallic Acid on Fermentation Parameters, Protein Fraction, and Bacterial Community of Whole Plant Soybean Silage - Wang, Cheng; Zheng, Mingyang; Wu, Shuo; Zou, Xuan; Chen, Xiaoyang; Ge, Liangfa; Zhang, Qing (Frontiers in Microbiology, 2021)
Whole plant soybean (WPS) is a kind of legume resource with characteristics of high nutrition, large biomass, and wide distribution. In the present study, we have investigated the feasibility and effects of gallic acid (GA) on WPS silage quality, nitrogen distribution, tannin content, and bacterial community. The 0.5 and 1% (fresh matter basis) GA were added into WPS for dynamic ensiling (days 3, 7, 14, and 30, respectively). The results showed that the WPS silage with GA addition significantly decreased pH value (6.16–5.38 at ensiling day 30), coliform bacteria count and butyric acid (65.3–62.0 g/kg dry matter at ensiling day 30), and amino nitrogen contents (259–88.2 g/kg total nitrogen at ensiling day 30) and promoted lactic acid (9.62–31.5 g/kg dry matter at ensiling day 30), acetic acid (24.1–85.6 g/kg dry matter at ensiling day 30), and tannin (total phenol and hydrolyzable tannin) contents. Additionally, the GA addition also contributed to the change of bacterial community, where Firmicutes and Lactobacillus were most abundant on phylum and genus levels, respectively. The above results suggested that GA additive applied in WPS silage was an effective strategy to protect nutrition and improve fermentation quality, and the 1% GA addition showed a better effect.